2022
DOI: 10.3390/ijerph192214948
|View full text |Cite
|
Sign up to set email alerts
|

Performing Arts in Suicide Prevention Strategies: A Scoping Review

Abstract: Suicide is a leading cause of death all over the world. Suicide prevention is possible and should be pursued through a variety of strategies. The importance of the arts for positive health outcomes has been increasingly evidenced. This scoping review aimed to identify the possible role of the performing arts—defined as a type of art performed through actions such as music, dance, or drama executed alive by an artist or other participant in the presence of an audience,—in suicide prevention programs. PubMed, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…This allowed drama therapy to be studied with a comprehensive approach to the diverse context of the field’s development, as well as its integration into other professional fields. The manual review of documents excluded studies that were not related to drama therapy ( n = 6; Johnston, 2009 ; Blencowe et al, 2018 ; Kawano et al, 2018 ; Suh et al, 2021 ; Davico et al, 2022 ). This phase of the study was triangulated twice - the first time after reading the study titles, keywords, and abstracts, but the second time after reading the content of the controversial studies.…”
Section: Methodsmentioning
confidence: 99%
“…This allowed drama therapy to be studied with a comprehensive approach to the diverse context of the field’s development, as well as its integration into other professional fields. The manual review of documents excluded studies that were not related to drama therapy ( n = 6; Johnston, 2009 ; Blencowe et al, 2018 ; Kawano et al, 2018 ; Suh et al, 2021 ; Davico et al, 2022 ). This phase of the study was triangulated twice - the first time after reading the study titles, keywords, and abstracts, but the second time after reading the content of the controversial studies.…”
Section: Methodsmentioning
confidence: 99%
“…The authors observed that while other countries have engaged in the adjudication process, there remains a focus on addressing the necessities that are worthwhile to improve the adjudication system. Indeed, the adjudication of cultural events serves not only to equip students with lifelong skills but also to teach them how to manage nervous energy effectively to achieve desired outcomes (Nussbaum, 2023;Davico et al, 2022). Additionally, the adjudication of cultural events acts as a motivational tool for students, encouraging them to dedicate more time to practice and advocating for the inclusion of music education programmes at both national, municipal and district levels (Hedgecoth & Major, 2019).…”
Section: Necessities Of Adjudication Of Cultural Eventsmentioning
confidence: 99%